A holistic evaluation of Greek municipalities' websites. (6th April 2009) - Chatzopoulos, Kariofillis-Christos; Economides, Anastasios A.
This paper investigates the state of municipalities' websites in 50 major Greek cities. First, it presents GovQual, a comprehensive evaluation framework which consists of 140 criteria organised into 13 evaluation categories. Then, 15 trained students evaluated 50 Greek municipalities' sites using GovQual. The results identified significant shortages related to the sites' interactivity and feedback, as well as e-services and applications. Differences among the various Greek geographical regions were also identified. Regions that are economically poor and faraway from the capital came behind. Suggestions for improvement and directions for future research are given.